Bioremediation of Soils Contaminated with Aromatic Compounds - Heipieper, Hermann J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
The present book represents a compilation of the major contributions of a NATO workshop on: Bioremediation of soils contaminated with aromatic compounds and took place in Tartu, Estonia. It demonstrated the importance and necessity of interdisciplinary research in modern environmental biotechnology. Next to the classical fields (microbiology, biochemistry, molecular biology) other aspects such as genome analysis and bioinformatics will become much more important in the near future. All aspects of this development are represented in this volume. Therefore, it can be seen as a major step forward as it fostered an intensive discussion between scientists of all these fields of environmental biotechnology.
BIOREMEDIATION OF SOILS CONTAMINATED WITH AROMATIC COMPOUNDS: EFFECTS OF RHIZOSPHERE, BIOAVAILABILITY, GENE REGULATION AND STRESS ADAPTATION -- INFLUENCE OF THE RHIZOSPHERE ON THE BIODEGRADATION OF ORGANIC XENOBIOTICS - A CASE STUDY WITH 2,4-DICHLOROPHENOXYACETIC ACID -- REGULATION OF THE ATRAZINE DEGRADATIVE PATHWAY IN Pseudomonas -- THE ROLE OF PLANTS AND BACTERIA IN PHYTOREMEDIATION - KINETIC ASPECTS -- REGULARITIES IN THE OXIDIZING METABOLISM OF BACTERIA -- FORMATION OF MICROBIAL COMMUNITIES IN OIL SHALE CHEMICAL INDUSTRY SOLID WASTES DURING PHYTOREMEDIATION AND BIOAUGMENTATION -- STUDIES ON BIODEGRADATION OF AROMATIC POLLUTANTS BY TRICHOSRORON CUTANEUM YEAST STRAIN -- THE POTENTIAL OF KERATINOLYTIC AND KERATINOPHILIC FUNGI FOR DEGRADATION OF PETROLEUM HYDROCARBONS IN SOIL -- STUDY OF CONTAMINATION AND MIGRATION POLYCHLORINATED BIPHENYLS IN THE ENVIRONMENT. BIOREMEDIATION OF CONTAMINATED SOILS AND ASSESSMENT OF THEIR IMPACT ON THE SERPUKHOV POPULATION HEALTH -- SHEDDING LIGHT ON THE BIOAVAILABILITY OF ORGANIC POLLUTANTS -- REDUCTION OF CHROMIUM (VI) BY BACTERIA COLLECTION STRAINS OF DIFFERENT PHYSIOLOGICAL GROUPS.
Keywords: ENVIRONMENTAL SCIENCES; MICROBIOLOGY; BIOTECHNOLOGY; ENVIRONMENT; ENVIRONMENTAL ENGINEERING/BIOTECHNOLOGY.; APPLIED MICROBIOLOGY